Development Of Optical Fiber Vis-Nir Spectroscopy System For Metrological Analysis On Intrinsic Qualities Of Averrhoa Carambola L - Omar, Ahmad Fairuz (2012)
Optical measuring techniques are one of the methods that have shown promising results in non-destructive quality evaluation. In this research, several approach in quantifying fruits intrinsic quality have been successfully performed through absorbance, reflectance and interactance techniques via visible and near infrared spectral as well as novel application of monochromatic measurement systems. The research begins by Aquaphotomics assessment (NIR absorbance) of water-sugars (sucrose, glucose and fructose) and water-acids (citric, tartaric, malic and oxalic) solutions which are common biochemical composition in fruits.